Quality Management Practices and Organizational Performance: Impact of Sustainable Product Development - Ahmad, Mohd Akhir; Mohd Asaad, Mohd Norhasni; Saad, Rohaizah; Iteng, Rosman; Abdul Rahim, Mohd Kamarul Irwan (ExcelingTech Publishers, 2016)
Competition among the automotive industry has encouraged companies to implement quality management practices in all managerial aspects to ensure customer and stakeholder satisfactions. Therefore, guaranteeing only product quality is insufficient without considering sustainable product development, which involves economic, environment, and social elements. Companies that meet both objectives gain advantages in the challenges business sustainability. This study addresses the issues regarding quality management practices, sustainable product development on organizational performance in small and mediumsized enterprises in the Malaysian automotive industry. A research was carried out in 91 SMEs automotive suppliers in throughout Malaysia. The analyzed using SPSS version 23. The study revealed that sustainable product development is the full mediating relationship between quality management practices and organizational performance. Thus, it contributes in the automotive industry that strategies of sustainable product development have an impact on organizational performance